Cord blood stem cells medicine - Stavropoulos-Giokas, Catherine; Charron, D. (Dominique); Navarrete, Cristina (Elsevier, Academic Press, 2015)
Cord Blood Stem Cells and Regenerative Medicine discusses the current applications for cord blood stem cells and techniques for banking cord blood. Cord blood, blood from the umbilical cord and placenta of an infant, represents an alternate source of stem cells that can be used to treat a myriad of disorders. Cord blood stem cells are being used more frequently and studied more seriously, as evidenced by the explosion of scientific literature on the topic. Currently, clinical and pre-clinical trials are being done in the field, treating conditions as severe as heart failure